Kewewenangan Mahkamah Konstitusi dalam Pembubaran Partai Politik di Indonesia - Bustanul Arifin (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2020)
One of the authorities of the Constitutional Court is to dissolve political parties on the basis that the political parties have principles, ideology, purposes and have committed violations that are contrary to the Pancasila and the 1945 Constitution. The purpose of this paper is to highlight the authority of the Constitutional Court in the dissolution of the political parties in Indonesia in the perspective of Islamic law. The conclusion of this paper is that the authority of the Constitutional Court in the dissolution of the political parties in the review of Islamic law is permissible as long as the political parties have already had principles, ideology, objectives and have violated the rules of a country. This, in Islam, can be claimed that the political parties have committed bughat or defiance of the state. In this case, the political parties are considered not to obey to a legal leader. Furthermore, the Constitutional Court in Indonesia, with its authorities, has in common or resembles a judicial institution in Islam called Wilayah al-Mazalim.